Parsley Health: Feasibility and acceptability of a large-scale holistic telehealth program for chronic disease care - Williams, Hants; Steinberg, Sarah; Vingum, Ryan; Leon, Kendall; Céspedes, Elena; Berzin, Robin; Hagg, Heather (Frontiers in Digital Health, 2023)
Background: A holistic, personalized approach to medicine can be used to prevent and manage a variety of chronic diseases. However, effectively managing chronic diseases can be difficult due to barriers related to insufficient provider time, staffing, and lack of patient engagement. To address these challenges telehealth strategies are being increasingly adopted, yet few studies have explored how to evaluate the feasibility and implementation success of large-scale holistic telehealth models for chronic disease care. The aim of this study is to assess the feasibility and acceptability of a large-scale holistic telehealth program for the management of chronic diseases. Methods: Data was collected from participants enrolled in a Parsley Health membership from June 1, 2021 to June 1, 2022, a subscription-based holistic medicine practice designed to help people prevent or manage chronic diseases. Implementation outcome frameworks were used to understand engagement with services, participant satisfaction, and preliminary effectiveness of the program via a patient-reported symptom severity tool. Results: Data from 10,205 participants with a range of chronic diseases were included in our analysis. Participants averaged 4.8 visits with their clinical team and reported high levels of satisfaction with their care (average NPS score of 81.35%). Preliminary evidence also showed substantial reduction in patient reported symptom severity. Conclusion: Our findings suggest the Parsley Health program is a feasible and acceptable large-scale holistic telehealth program for chronic disease care. Successful implementation was due, in part, to services that promoted participant engagement along with tools and interfaces that were helpful and easy to use.